2009
DOI: 10.1002/jbm.a.32532
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of highly macroporous ceramic scaffolds for bone tissue engineering

Abstract: During the last decades, different materials of both natural and synthetic origin have been developed with the aim of inducing and controlling osteogenic differentiation of mesenchymal stem cells (MSCs). In order for that to happen, it is necessary that the material to be implanted obey a series of requirements, namely: osteoconduction, biocompatibility, and biodegradability. Additionally, they must be low-priced, easy to produce, shape, and store. Hydroxyapatite (HA) is a well known ceramic with a composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…The possibility of culturing cell seeded scaffolds for at least 5 days provides an advantage for tissue engineering purposes. In bone tissue engineering, for instance, the in vivo bone forming potential of cells is often assessed by seeding them on scaffolds, followed by in vitro culture for 7 days prior to implantation in an animal model [26]. Researchers frequently use scaffolds with poorly defined architectures, which compromises the quality of the tissue engineered grafts and the success of in vivo bone formation.…”
Section: Static Culturing Of Imsc On the Different Scaffoldsmentioning
confidence: 99%
“…The possibility of culturing cell seeded scaffolds for at least 5 days provides an advantage for tissue engineering purposes. In bone tissue engineering, for instance, the in vivo bone forming potential of cells is often assessed by seeding them on scaffolds, followed by in vitro culture for 7 days prior to implantation in an animal model [26]. Researchers frequently use scaffolds with poorly defined architectures, which compromises the quality of the tissue engineered grafts and the success of in vivo bone formation.…”
Section: Static Culturing Of Imsc On the Different Scaffoldsmentioning
confidence: 99%
“…Despite the advantages, hydroxyapatite use has been limited because of its brittle nature, low tensile strength, and high infection rates (Table 1). Hydroxyapatite has demonstrated osteointegration in animal models; 19,21,26 however, there is not much evidence for osteointegration for humans in vivo. 9 Frassanito et al demonstrated that hydroxyapatite may break down into many fragments over time in vivo, and they also demonstrated extremely limited osteointegration that lacked lamellar organization.…”
Section: Hydroxyapatitementioning
confidence: 99%
“…It though has disadvantages like, low tensile strength, high infection, brittleness, disintegration with time and unpredictable response when exposed to blood or cerebrospinal fl uid. 14,23,33 Patients with hydroxyapatite must stay away from trauma till full bone is formed.…”
Section: Hydroxyapatitementioning
confidence: 99%